KEJADIAN BERAT BADAN LAHIR RENDAH DI DESA TINELO KABUPATEN GORONTALO DAN FAKTOR YANG MEMENGARUHINYA - Nuryani, Nuryani; Rahmawati, Rahmawati (Jurnal Gizi dan Pangan, 2017)
The aim of this study was to assess the association of maternal age, education level and family income with low birth weight (LBW). The study was an observational study with cross sectional design. The number of subject were 60 children under five years old obtained by accidental sampling. The results showed that 18.3% of mothers gave birth at high risk age (≤19 years old and ≥35 years old), 43.3% mothers had education level of senior high school, 96.7% mothers were housewives, 54.2% father’s occupation was self-employed, 71.7% of family income per month was under minimum regional wage. 16.7% of infants with LBW. The bivariate analysis showed that the incidence of low birth weight was not associated with maternal age (p=0.371), there was no correlation between the incidence of low birth weight with family income per month (p=0.709) and there was correlation between low birth weight with mother education level (p=0.017). It can be concluded that maternal age and family income per month was not associated with LBW, while education level was associated with LBW.